2022
DOI: 10.1111/infa.12460
|View full text |Cite
|
Sign up to set email alerts
|

Not all babies are in the same boat: Exploring the effects of socioeconomic status, parental attitudes, and activities during the 2020 COVID‐19 pandemic on early Executive Functions

Abstract: Early executive functions (EFs) lay the foundations for academic and social outcomes. In this parent-report study of 575 UK-based 8-to 36 month olds (218 followed longitudinally), we investigate how variation in the home environment before and during the 2020 pandemic relates to infants' emerging EFs. Parent-infant enriching activities were positively associated with infant Cognitive Executive Function (CEF) (encompassing inhibitory control, working memory, cognitive flexibility). During the most-restrictive U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 104 publications
(159 reference statements)
8
39
2
Order By: Relevance
“…It is not yet known whether these effects will be sustained over a longer period, or whether the benefits of parent-child enriching activities are specific to older toddlers compared with infants. To date, sex differences in these effects have not been reported Hendry et al, 2022, Rosen et al, 2020 . Engagement in parent-child activities may also be expected to support the development of social competence (i.e., engagement in pro-social behaviours such as sharing readily and being considerate of others' feelings).…”
Section: Enriching Activitiesmentioning
confidence: 95%
See 4 more Smart Citations
“…It is not yet known whether these effects will be sustained over a longer period, or whether the benefits of parent-child enriching activities are specific to older toddlers compared with infants. To date, sex differences in these effects have not been reported Hendry et al, 2022, Rosen et al, 2020 . Engagement in parent-child activities may also be expected to support the development of social competence (i.e., engagement in pro-social behaviours such as sharing readily and being considerate of others' feelings).…”
Section: Enriching Activitiesmentioning
confidence: 95%
“…Cross-sectional research also points to an important but less wellstudied link between screen use and social competence (Wan et al, 2021). During the specific context of the pandemic, the amount of time that parents reported that their child spent engaged with a screen showed a small negative association with child executive functions (Hendry et al, 2022); what is not yet known is whether these effects are pervasive over a longer period, particularly after taking into account other aspects of the home environment.…”
Section: Screen Usementioning
confidence: 99%
See 3 more Smart Citations